Eksplorasi Pemanfaatan Alat Musik Keteng-Keteng Sebagai Media Pembelajaran Bangun Ruang Sisi Lengkung Tabung di Kelas IX SMP - Sitepu, Edi Petra; Tambunan, Hardi; Pangaribuan, Firman (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to describe the use of keteng-keteng musical instruments as a medium for teaching mathematics on the subject of curved tube shapes in ninth grade junior high school. The study uses a descriptive qualitative approach with ninth grade junior high school students as the research subjects. Data collection was carried out through observation of the learning process, interviews with students and teachers, and documentation of learning activities. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing using triangulation techniques to maintain data validity. The results showed that the use of keteng-keteng musical instruments helped students understand the concept of cylinders more concretely through direct observation of the shape, elements, and characteristics of cylinders. In addition, the use of this locally-based media was able to increase student engagement, interest in learning, and activity in the mathematics learning process. Thus, the keteng-keteng musical instrument can be used as an alternative contextual and meaningful learning media for mathematics in the subject of curved tube shapes.